The Asymmetric Impact of Global Uncertainty on Energy Consumption in the Gulf Cooperation Council Countries: A Panel Nonlinear Autoregressive Distributed Lag Approach - Elroukh, Ahmed W. (International Journal of Energy Economics and Policy, 2025)
This study investigates the relationship between uncertainty and energy consumption in the Gulf Cooperation Council (GCC) countries, focusing on the potential asymmetry in this relationship. Utilizing annual data from 1997 to 2023, the analysis uses both linear and nonlinear panel autoregressive distributed lags (ARDL) models, estimated with the Pooled Mean Group method that assumes long-run homogeneity across the individual countries which is suitable in this framework given the similarity across the GCC countries. The linear ARDL results suggest no significant effect of uncertainty. However, once asymmetries are introduced, the findings show that in the short-run rising uncertainty tends to reduce energy demand, while falling uncertainty has little to no impact. By using a country-specific uncertainty measure and accounting for asymmetric effects, the study offers new insights into energy use dynamics in oil-reliant economies.